The last dragon - De Mari, Silvana (Miramax Books, Hyperion Books for Children, 2007)
Struggling to survive in a post apocalyptic world after his village is destroyed, Yorsh, the earth's last elf, must embark on a perilous quest to decipher a powerful prophecy and find the last dragon, who holds the key to saving the world from the Dark Age that has begun.